Clinical Outcome of Urgent Thoracotomy in Patients with Penetrating and Blunt Chest Trauma: A Retrospective Survey - Refaely, Yael; Koyfman, Leonid; Friger, Michael; Ruderman, Leonid; Saleh, Mahmud Abu; Sahar, Gidon; Shaked, Gad; Klein, Moti; Brotfain, Evgeni (The Thoracic and Cardiovascular Surgeon, 2018)
Introduction In contrast to an emergency department of thoracotomy (EDT), an urgent thoracotomy (UT) is defined as a surgical thoracic intervention performed in the operating room within the first 48 hours of the patient's intensive care unit (ICU) stay. The factors affecting survival after UT are not fully understood. In this study, we retrospectively analyzed the clinical data and outcome of patients with blunt and penetrating chest injuries who underwent UT.Methods All adult patients who had blunt or penetrating chest trauma and who underwent UT, were included in the study. All data were collected from the patients' hospital and ICU records. Forty-five patients with thoracic injuries who underwent UT during the first 48 hours of ICU stay were analyzed. Of these, 25 had penetrating chest injuries, and 20 had blunt thoracic injuries. Of the penetrating injuries, 16 were stab wounds, and 9 were gunshot wounds.Results Overall ICU mortality was 29% (n = 13) and was significantly higher in the blunt chest trauma group than in the penetrating trauma group (45% vs 16%; p = 0.04). Lung parenchyma injuries (lacerations and contusions) were the most common intraoperative findings in both groups. The following independent predictors of in-hospital mortality were found: an Injury Severity Score (ISS) of >40; an Acute Physiology and Chronic Evaluation II (APACHE II) score of >30; prolonged duration of UT; low body temperature on admission to the ED; abnormal arterial blood lactate, bicarbonate, and pH at the end of UT; and use of vasopressors during the first 24 hours of ICU stay.Conclusion Mortality after UT was higher in patients with blunt chest trauma. The UT should be performed in both penetrating and blunt chest trauma as quickly as possible and should be limited to damage control. It also emerges that acidosis and hypothermia in chest trauma patients need to be treated extremely aggressively before, during, and after UT.
Keywords: urgent thoracotomy; blunt chest trauma; penetrating chest trauma emergency thoracoscopy